The one and only Ivan - Applegate, Katherine; Castelao, Patricia (New York : Harper, 2012)
When Ivan, a gorilla who has lived for years in a down-and-out circus-themed mall, meets Ruby, a baby elephant that has been added to the mall, he decides that he must find her a better life.
Newbery Medal/Honor
School Library Journal starred
Wilson's Children
Booklist, February 2012
Bulletin of the Center for Children's Books starre, February 2012
Horn Book, November 2012
Keywords: Animal welfare -- Juvenile fiction; Elephants -- Juvenile fiction; Gorilla -- Juvenile fiction; Animals -- Treatment -- Fiction; Elephants -- Fiction; Gorilla -- Fiction; Animal welfare -- Fiction; Elephants -- Fiction; Gorillas -- Fiction